Tamizaje fitoquímico y actividad antibacteriana del extracto etanólico del fruto verde de Genipa americana L. (huito) - Macedo Gutierrez, Milagros Raquel (2022)
Determining the in vitro antibacterial activity of plant species is a global challenge and their study and research allows knowing which species are potential antimicrobials. The objective of the present work was to identify the secondary metabolites of the ethanolic extract of the green fruit of Genipa americana L. by phytochemical screening and to determine their antibacterial activity against control strains and clinical isolates of Staphylococcus aureus ATCC 25923, Pseudomonas aeruginosa ATCC 27853 and Escherichia coli ATCC 25922. For this research, the phytochemical screening methods and the Kirby-Bauer Diffusion method were used. The following secondary metabolites were identified by phytochemical screening: triterpenes and/or steroids, flavonoids, leucoanthocyanidins, cardiotonic glycosides, phenols and/or tannins, fatty compounds, saponins, lactones, and reducing sugars. The Kirby-Bauer Diffusion Method established that the ethanolic extract was not active against any of the control strains and clinical isolates under study at concentrations of 125 mg/mL, 62.5 mg/mL and 31.25 mg/mL. For this reason, the ethanolic extract of G. americana L. does not present antibacterial activity against the above mentioned microorganisms.